Analisis Kesalahan Berbahasa pada Teks Pidato Persuasif Siswa Kelas 9J SMPN 9 Tasikmalaya - Assyifa Rahman; Sabrina Fajriani Nuramali; Resha Zakiyatussolihah; Ai Siti Nurjamilah (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research is entitled "Analysis of language errors in persuasive speech texts for class 9J students at SMPN 9 Tasikmalaya". The aim of this research is to find out language errors in persuasive texts. The approach used in this research is a qualitative descriptive approach. The data used in the research are words in persuasive texts that experience errors in aspects of phonology, morphology and spelling. The technique used in this research is the listening and note-taking technique. This listening technique is used to obtain data by reading and listening to the use of language in the form of speech texts written by students, then the note-taking technique, namely writing down errors in the speech texts written by students. The results of the research show that the types of language errors that are most often found are errors in word usage, word selection and sentence construction that do not comply with correct Indonesian language rules. Factors causing this error include students' lack of understanding of language rules, as well as the influence of informal, everyday language habits. It's hoped that this research can provide insight into teaching Indonesian in schools, especially in improving the quality of students' written persuasive texts..